Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/neuonc/nov098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging correlates of tryptophan metabolism via the kynurenine pathway in human meningiomas

Abstract: PET imaging of tryptophan metabolism can provide quantitative imaging markers for differentiating grade I from grade II/III meningiomas. TDO2 may be an important driver of in vivo tryptophan metabolism in these tumors. These results can have implications for pharmacological targeting of the KP in meningiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
(62 reference statements)
3
38
0
1
Order By: Relevance
“…Nevertheless, the high 18 F-FETrp uptake in the bladder and pancreas suggests that this tracer would not allow visualization of tumors in these organs because of high background activity. Despite the differences in distribution, both tracers demonstrated similarly low and continuous brain accumulation, suggesting that 18 F-FETrp will be suitable for the imaging of intracranial brain tumors as previously established with 11 C-AMT (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Radiation Dosimetry For 18 F-fetrpmentioning
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, the high 18 F-FETrp uptake in the bladder and pancreas suggests that this tracer would not allow visualization of tumors in these organs because of high background activity. Despite the differences in distribution, both tracers demonstrated similarly low and continuous brain accumulation, suggesting that 18 F-FETrp will be suitable for the imaging of intracranial brain tumors as previously established with 11 C-AMT (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Radiation Dosimetry For 18 F-fetrpmentioning
confidence: 79%
“…The total injected activity in mice for the 18 F-FETrp tracer was between 5.5 and 9.2 MBq (150-250 mCi), a dose commonly used in smallanimal PET studies of mice using 18 F-labeled PET tracers (39,40). Because of the shorter half-life of the 11 C isotope (20 min), a higher activity was administered in the AMT study (20)(21)(22) MBq equivalent to 550-600 mCi). This dose was previously determined by our group as sufficient to obtain high-quality images in the PDX tumor models (35).…”
Section: Small-animal Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…14 AMT-PET can detect and differentiate various primary and metastatic brain tumors, including glioblastomas. 1517 We have also demonstrated that high tryptophan uptake in the suspected recurrence site was a strong prognostic imaging marker for 1-year and overall survival in patients with previously-treated glioblastoma independent of MRI and clinical prognostic factors. 18 However, PET findings were not correlated with molecular prognostic markers, and the potential prognostic value of AMT-PET in pre-treatment glioblastomas remained to be determined.…”
Section: Introductionmentioning
confidence: 76%
“…Dynamic PET imaging provides information on the temporal characteristics of radiotracer distribution and allows PET tracer kinetic analysis for separation of tumoral tracer transport and trapping; for some tracers, the source of some of the trapped radioactivity is from metabolites. For example, in the case of the tryptophan derivative AMT, the tracer may undergo metabolism via the serotonin and also by the immunosuppressive kynurenine pathway [7, 9,16]; the latter is commonly upregulated in a variety of tumors, including gliomas, glioneuronal tumors and meningiomas [1,3,7,42]. AMT was shown to have a differential uptake in a variety of gliomas [13].…”
Section: Pet Imaging In Pretreatment Evaluation Of Pediatric Gliomasmentioning
confidence: 99%